Integrating Multiple Intelligence Learning Approach to Upgrade Students’ English Writing Skills - Hasbullah Hasbullah; Nur Wahidah; Nanning Nanning (Universitas Negeri Makassar, 2023)
The educational curriculum’s current challenge is to use appropriate approaches during the Covid-19 days. This study aimed to investigate the multiple intelligence learning approaches (MILA) which were used to provide students’ competence in English writing skills in an institute of IAIN Sorong, West Papua Province, Indonesia. In terms of it the multiple intelligence learning approaches introduced interactive, analytic, and introspective domains which cover elements of linguistics, mathematics, visual, kinesthetic, music, intra-personal, interpersonal, naturalistic, and existential or spiritual. Those elements would be appropriately implemented to upgrade students’ English writing skills. This study employed a survey method using lists of questionnaires to obtain qualified data which were collected through eight English lecturers, four staff curriculum developers, and eighty students. The findings conclude that most respondents felt contented and interested in developing and upgrading English writing skills using the Multiple Intelligence Learning Approaches. The results of this research claimed that the lecturers require the MILA to be more widely used to upgrade students’ writing skills. Also, the practitioners on campus should make together the strategies to be included in MILA for teaching English writing skills as recommended by the national education curriculum.